1986
DOI: 10.1002/ijc.2910380413
|View full text |Cite
|
Sign up to set email alerts
|

Two new cell lines from B‐prolymphocytic leukaemia: Characterization by morphology, immunological markers, karyotype and Ig gene rearrangement

Abstract: Leukaemic cells from 2 patients with B-prolymphocytic leukaemia were immortalized in vitro by means of Epstein-Barr virus and phorbol-ester TPA. The resulting cell lines, named JVM-2 and JVM-3, have been growing continuously in liquid culture for more than one year. JVM-2 is characterized cytogenetically by t(11;14)(q13; q32), and JVM-3 by trisomy 12. The immunoglobulin (Ig) heavy- and light-chain genes showed the same pattern of rearrangement in both lines as in the original prolymphocytes from each case. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…CLL cell lines (MEC1, JVM2, and JVM3), which were established from the peripheral blood of patients with CLL by EBV transformation (24,25), were obtained from the German Resource Centre for Biological Material and cultured in RPMI 1640 (Life Technologies, Inc.) supplemented with 10% FCS (Life Technologies), 1 mmol/L glutamine (Life Technologies), 1% penicillin/streptavidin (Life Technologies), and 25 mmol/L HEPES (Biochrom). TRAIL was obtained from R&D Systems, Inc., and the broad-range caspase inhibitor N-benzyloxycarbonyl-Val-Ala-Asp-fluoromethylketone (zVAD.fmk) was obtained from Bachem and used to determine the dependency of apoptosis on caspase activity.…”
Section: Methodsmentioning
confidence: 99%
“…CLL cell lines (MEC1, JVM2, and JVM3), which were established from the peripheral blood of patients with CLL by EBV transformation (24,25), were obtained from the German Resource Centre for Biological Material and cultured in RPMI 1640 (Life Technologies, Inc.) supplemented with 10% FCS (Life Technologies), 1 mmol/L glutamine (Life Technologies), 1% penicillin/streptavidin (Life Technologies), and 25 mmol/L HEPES (Biochrom). TRAIL was obtained from R&D Systems, Inc., and the broad-range caspase inhibitor N-benzyloxycarbonyl-Val-Ala-Asp-fluoromethylketone (zVAD.fmk) was obtained from Bachem and used to determine the dependency of apoptosis on caspase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Rec-1 and the myelomonocytic cell line U937 cells were maintained in RPMI 1640 medium supplemented with 2 mM L-glutamine and 10% fetal calf serum (FCS) and 50 g/ml gentamicin under standard conditions (humidified atmosphere, 95% air, 5% CO 2 , 37°C). The Epstein-Barr virus-negative MCL cell line JeKo (Jeon et al, 1998) and the JVM-2 cell line generated from a B-prolymphocytic leukemia (B-PLL) with t(11; 14)(q13;q32) (Melo et al, 1986) were kept under the same conditions except for supplementation with 20% FCS. Several studies have suggested that B-PLL is not a specific disease entity, but a blastic variant of a different lymphoma.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we knocked down the expression of PPP1CB using a lentivirus-based shRNA approach and evaluated its effects on cell proliferation in B-lymphocytic leukemia cell lines MEC1 (22) and JVM3 (24), as well as in National Institutes of Health (NIH) 3T3 and Ba/F3 cell lines. Water-soluble tetrazolium-1 (WST-1) cell proliferation assays demonstrated that in comparison with control (P < 0.01), knockdown of PPP1CB resulted in increased cell proliferation in NIH 3T3 and Ba/F3 cells (Fig.…”
Section: Validation Of Ypel5/ppp1cb and Reciprocal Fusion In Independentmentioning
confidence: 99%